Insect Diversity Study on Shallot Plants: Comparison of Ecological Engineering and Conventional Cultivation Systems - Amelia Seftiarini; Tri Mujoko; Wiwin Windriyanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study examines the cultivation of shallots using an ecological engineering approach to enhance insect diversity and natural pest control. The applied methods include compost application, refugia planting, and the use of biological agents to reduce synthetic pesticide dependence. The study compares two management systems: ecological engineering farmland (EF) and conventional farmland (CF), with insect data collected using various trapping methods. The results show that EF had a higher insect population (23,428 individuals) compared to CF (14,880 individuals). A total of 181 morphospecies from 10 orders, 85 families, and 170 genera were identified, with Coleoptera being the dominant order and predatory insects prevailing in both farmlands. The diversity index was higher in EF (3.079) than in CF (2.725). The evenness index was also higher in EF (0.608–0.624) than in CF (0.561–0.603), indicating a more stable ecosystem. The dominance index was low in both farmlands (0.003–0.188), showing no single species significantly dominated. The community similarity index was relatively high at 0.666 (vegetative), 0.651 (generative), and 0.712 (one growing season). Although the t-test showed no significant differences, EF tends supports more sustainable shallot farming by enhancing biodiversity and ecosystem stability. Further research is needed to evaluate long-term impacts and the implementation of polyculture systems to strengthen agricultural ecosystems.